Treatment with pembrolizumab in programmed death ligand 1–positive recurrent glioblastoma: Results from the multicohort phase 1 KEYNOTE‐028 trial. Issue 10 (26th January 2021) - Reardon, David A.; Kim, Tae Min; Frenel, Jean‐Sebastien; Simonelli, Matteo; Lopez, Juanita; Subramaniam, Deepa S.; Siu, Lillian L.; Wang, Hui; Krishnan, Suba; Stein, Karen; Massard, Christophe
Abstract : Background: Current treatments for recurrent glioblastoma offer limited benefit. The authors report the antitumor activity and safety of the anti–programmed death 1 (anti–PD‐1) immunotherapy, pembrolizumab, in programmed death ligand 1 (PD‐L1)–positive, recurrent glioblastoma. Methods: Adult patients with PD‐L1–positive tumors were enrolled in the recurrent glioblastoma cohort of the multicohort, phase 1b KEYNOTE‐028 study (ClinicalTrials.gov identifier, NCT02054806) and received pembrolizumab 10 mg/kg every 2 weeks for up to 2 years. The primary endpoint was investigator‐assessed overall response rate according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Archival tumor samples were assessed for PD‐L1 expression levels (prospectively) and T‐cell–inflamed gene expression profile score (retrospectively). Results: After a median follow‐up of 14 months (range, 2‐55 months) among the 26 enrolled patients, the overall response rate was 8% (95% CI, 1%‐26%). Two partial responses, lasting 8.3 and 22.8 months, occurred. Progression‐free survival (median, 2.8 months; 95% CI, 1.9‐8.1 months) rate at 6 months was 37.7%, and the overall survival (median, 13.1 months; 95% CI, 8.0‐26.6 months) rate at 12 months was 58%. Correlation of therapeutic benefit to level of PD‐L1 expression, gene expression profile score, or baseline steroid use could not be established. Treatment‐related adverse events occurred in 19 patients (73%), and 5 patients experienced grade 3 or 4 events (there were no grade 5 events). Immune‐mediated adverse events and infusion reactions occurred in 7 patients (27%). Conclusions: Pembrolizumab monotherapy demonstrated durable antitumor activity in a subset of patients with manageable toxicity in this small, signal‐finding, recurrent glioblastoma cohort. Future studies evaluating rationally designed pembrolizumab combination regimens may improve outcomes in patients with recurrent glioblastoma. Abstract : In the phase 1 multicohort KEYNOTE‐028 study (ClinicalTrials.gov identifier, NCT02054806), the antitumor activity and safety of pembrolizumab were evaluated among patients with recurrent glioblastoma. Pembrolizumab monotherapy demonstrates antitumor activity in a subset of patients and has acceptable toxicity in this setting, in which current treatment options provide limited benefit and the prognosis is poor.